A Preliminary Study of the Forest Typology of Jammu and Kashmir - Ullar, Mir Inayat; Ticku, B. L. (Indian Forester, 1964)
An attempt has been made in this paper to describe the vegetation of Jammu and Kashmir State with reference to its composition, distribution and ecology of the forest Effort has been made to discuss the classification with climate as denominator in accor dance with the floristic scheme of Champion, which being obviously extensive, an intensive effort on the same foundation has been made based on available information and observations. While the authors do not claim this dissertation as the last word on the typology of the forests of Jammu and Kashmir, any suggestions for improvement are most welcome.